The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.16986/huje.2015014224
|View full text |Cite
|
Sign up to set email alerts
|

Resimli Çocuk Kitaplarının İçerik ve Resimleme Özelliklerinin Bazı Değişkenler Açısından İncelenmesi

Abstract: yılları arasında Türkiye'de yayınlanan resimli çocuk kitaplarının içerik ve resimleme özelliklerinin incelenmesi bu araştırmanın problemini oluşturmaktadır. Araştırmada tarama-betimleyici yöntem kullanılmıştır. Araştırmanın kuramsal kısmı için kaynaklar taranıp, bilgiler derlenmiştir. 2000-2010 yılları arasında yayımlanan okul öncesi öykü kitaplarından oluşan 150 kitaba, hazırlanan kitap inceleme formu uygulanmıştır. Kitap inceleme formu ile kitapların fiziksel, resimleme, içerik ve karakter özellikleri incele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
1
7

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 1 publication
0
6
1
7
Order By: Relevance
“…The first research question which sought to find out the PTs' evaluation regarding the quality of their picture story books in terms of some basic literary elements revealed positive results in general. In line with the study of Gönen et al (2012) which examined 120 picture books and reported that most of the stories were high quality in terms of matching the images with the texts, the books created in this study were considered as high quality both by the authors and the experts in point of creating scripts with well-matched images with the tastes of children and with the educational requirements of the curriculum units. What is more about the stories created in this study is that the participants tried to expand the meaning of the texts not only through pictures but also some tactual materials such as attachable puppets (see appendix 1), puzzles and maps.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…The first research question which sought to find out the PTs' evaluation regarding the quality of their picture story books in terms of some basic literary elements revealed positive results in general. In line with the study of Gönen et al (2012) which examined 120 picture books and reported that most of the stories were high quality in terms of matching the images with the texts, the books created in this study were considered as high quality both by the authors and the experts in point of creating scripts with well-matched images with the tastes of children and with the educational requirements of the curriculum units. What is more about the stories created in this study is that the participants tried to expand the meaning of the texts not only through pictures but also some tactual materials such as attachable puppets (see appendix 1), puzzles and maps.…”
Section: Discussionmentioning
confidence: 81%
“…Reviewing the related literature, the researcher found out that trade picture books have been examined in different studies from various perspectives by taking both literature and art into account (Catalano, 2005;Çer & Şahin, 2016;Gönen, Uygun, Erdoğan & Katrancı, 2012;Maria, 2016;Wagner, 2013;Wu, 2014). Notwithstanding, there appears a gap in the literature with regard to the evaluation of teacher generated and context specific picture story books aiming to promote children's foreign language development.…”
Section: Children Literature: Picture Story Booksmentioning
confidence: 99%
See 1 more Smart Citation
“…Erdogan (1999), observed that there are qualitative and quantitative deficiencies, Çakmak (1994) and Demircan (2006), found out that some books do not have sufficient criteria under the titles of child illustration and physical characteristics, text and image relation, binding, cover quality, language and expression. Karakuş, Uysal, Kehci, Ulutaş, & Kahve (2016) identified problems with the content and illustration features of illustrated children's books, Gönen, Uygun, Erdoğan and Katrancı (2012) stated that illustrated children's books do not use durable skin, there is no subject diversity and three quarters of the images are imaginary. They determined that the ratio of text / image was not at the desired level.…”
Section: Introductionmentioning
confidence: 99%
“…Çocuk edebiyatına yönelik ders kitaplarının içeriklerine bakıldığında çocuk kitaplarının biçim ve içerik özellikleri açısından taşıması gereken niteliklere önemli ölçüde yer verildiği (örn. ; Akbayır, 2010;Aytekin, 2016;Oğuzkan, 2013;Temizyürek, Şahbaz ve Gürel, 2016;Yılar ve Celepoğlu, 2015); edebî eserleri incelemeye yönelik akademik çalışmalarda ise bu eserlerin çeşitli açılardan çocuğa uygunluğunu ve çocukta geliştirilmesi öngörülen beceri ve değerler açısından yeterliliğini konu edinen çok sayıda araştırmanın olduğu (örn., Aslan, 2007;Ateş, 2012;Arpacı, 2008;Bilgin, 2011;Canlı ve Aslan, 2018;Çatalcalı-Soyer, 2009;Dağlıoğlu ve Çakmak, 2009;Demircan, 2006;Genç ve Yalınkılıç, 2011;Gönen, Katrancı, Uygun ve Uçuş, 2011;Gönen, Karakuş, Uysal, Kehci, Ulutaş ve Kahve, 2015;Kara, 2012;Koçağan, 2012;Maden, 2007;Özer, 2006;Özgider, 2010;Tuncer, 2016;Ulutaş, 2017;Yükselen, Şenol, Üstündağ ve Ay, 2017) (Gültekin, 2006;Uğurlu, 2010;Yazıcı, 2013a).…”
Section: Introductionunclassified